Thermal performance of horizontal closed-loop oscillating heat pipes - Piyanun Charoensawan (2018)
This research aims to experimentally investigate the thermal performance of a horizontal closed-loop oscillating heat pipe (HCLOHP) at normal operating condition. The tested HCLOHPs were made of copper capillary tubes with various inner diameters, evaporator lengths and number of turns. The working fluids used within the HCLOHPs were distilled water and absolute ethanol, which were added into the tubes to various filling ratios. The evaporator sections of the HCLOHPs were heated by electric strip heaters. The heat was removed from the condenser sections by forced convective heat transfer of ambient air blowing through the sections. The adiabatic sections were well insulated by foam insulators. The thermal performance of the HCLOHPs was evaluated by calculating the rate of heat transferred to the ambient air at the condenser. It was found from all the experimental results that the operation start-up of a HCLOHP depends on the evaporator temperature that is related to the number of turns. The critical number of turns depends on the evaporator temperature and the inner diameter of the tube. The thermal performance of a HCLOHP improves by increasing the evaporator temperature and decreasing the evaporator/effective length. The best performance of all the HCLOHPs occurred at the maximum number of 26 turns. The proper filling ratio for a HCLOHP with a 150 mm Leis 30% and for a 50 mm Leis both 30% and 50%. The proper working fluid for a HCLOHP with a 2 mm inner diameter is water, but for those with a 1 mm inner diameter both water and ethanol are appropriate. © 2007 Elsevier Ltd. All rights reserved.